Local Teachers’ perceptions of adaptation to the IB MYP schools in Azerbaijan - Ismayilov, Namig; Safarli, Leyla; Bakhshiyeva, Matanat (My University, 2026)
The growing implementation of the International Baccalaureate Middle Years Programme (IB MYP) in Azerbaijan has influenced the recruitment of local teachers into international school settings. The purpose of this study is to investigate how local teachers in Azerbaijan perceive their adjustment to IB MYP schools and how professional support following hiring affects this process. Despite growing research on the transformative effects of IB programmes on pedagogy, teacher identity, and instructional practices, little is known about how locally recruited teachers experience adaptation in emerging IB contexts such as Azerbaijan. This study addresses that gap by exploring local teachers' perceptions of their transition into IB MYP schools and the role of professional support in shaping that process, and it contributes to the limited literature on teacher adaptation and professional transition within developing international education contexts. This qualitative study employed semi-structured interviews with eight local teachers selected via purposive sampling and two school leaders from IB MYP schools recruited via convenience access in Azerbaijan. Data were analyzed using thematic analysis. Findings revealed that teachers experienced adaptation as a gradual and emotionally demanding process characterized by role ambiguity, inconsistent professional support, and significant professional identity transformation. Although the sample size allowed to explore participants' experiences in-depth, it limited the transferability of the findings beyond the participating schools. The study highlights the importance of structured induction, mentoring, and professional development in supporting local teachers' adaptation to IB MYP environments.